(untitled) (Revista Educação, Artes e Inclusão, 2026)
This article arises from research aimed at comprehending the perceptions of both children and adults – encompassing the school director, project coordinator, teachers, and artistic mentors – regarding the RADIO(GRAFIAS) IGUAIS Project. Implemented in the 1st Cycle of Basic Education (1st CBE) at a school within a cluster located in the municipality of Amadora, Portugal, the study conducted focused group and individual interviews to ascertain (i) perceptions concerning artistic education within the 1st CEB curriculum and (ii) the participants’ assessment of the project. The results obtained facilitated the characterization of the understanding of the several participants regarding artistic education in the 1st CBE, delineated by five principal logics: compensatory action, community interaction, (non) curricular instrumentalization, (non) motivational instrumentalization, and the simultaneous assumption of roles. Overall, artistic education received acclaim from all participants, particularly among adults, highlighting the recognition of the inclusive and community potentials of the arts. Nevertheless, distinctions were noted in certain aspects, such as insufficient training in areas of artistic education or concerns about curriculum extension (teachers), difficulty in acknowledging artistic education areas as part of the curriculum (children), and challenges in coordinating all stakeholders and managing time (artistic mentors).